Implementasi metode pembelajaran project based learning berbasis teknologi canva untuk meningkatkan kreativitas peserta didik di sekolah menengah pertama - Pedhu, Romo Yoseph; Septianingsih, Dwidya; Burhanudin, Muhammad Zidane; Fawzia, Mairita; Irawati, Hefi; Wahyuni, Putri Astrivo (Education and Social Sciences Review, 2022)
In the current era of modern education, it is crucial to develop teaching strategies that foster students' creativity. One method that has garnered attention is Project-Based Learning (PjBL), which emphasizes project-based learning to enable students to learn through direct experience. Technology has also become an integral part of the learning process, allowing for better integration between innovative teaching approaches and available digital tools. In this context, the implementation of PjBL learning methods based on Canva technology can be an intriguing approach to enhance students' creativity. This research aims to explore and evaluate the implementation of PjBL learning methods based on Canva technology in enhancing the creativity of students at SMA Negeri 1 Tambun Selatan. The results of the study indicate that the use of PjBL learning methods based on Canva technology is effective in enhancing students' creativity. The integration of Canva technology allows students to create engaging and informative design, while the PjBL approach provides opportunities for students to learn through direct experience and become an interesting learning. Additionally, active student participation in the learning process, collaboration among peers, and the use of constructive feedback also contribute to enhancing their creativity.